2021
DOI: 10.1182/blood-2021-150888
|View full text |Cite
|
Sign up to set email alerts
|

Post Transplantation Fludarabine and Cyclophosphamide Selected and Promoted Low Dose of Unrelated UCB Implanation in Combined Transplantation of Haploid and UCB Stem Cells in Childhood Leukemia: 40 Cases Report in Double Center

Abstract: Background: For patients without HLA matched donor, Haploid stem cell transplantation with PTCY method has relatively higher risk of relapse and graft-versus-host disease (GVHD). Umbilical cord blood (UCB) is readily available and has helped expand the donor pool to almost all patients requiring a transplant. Meanwhile UCB transplant improves EFS in leukaemia with lower risk of relapse and GVHD. However, the clinical application of UCB is limited due to lower implantation rate because of its low dose of stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…High MNC of PBSC from relative donors combined with unrelated CB were applied. And PTCY with or without a low dose of ATG rather than a regular dose of ATG in vivo T cell depletion in haplo-HSCT in our study (Li et al, 2019;Xiao et al, 2021). Consistently, a series of studies support CMV infection occurred more frequently in haplo-HSCT due to delayed T-cell reconstitution (Dziedzic et al, 2017;Lin et al, 2019;Yokoyama et al, 2019;Solano et al, 2021;Cho et al, 2021).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…High MNC of PBSC from relative donors combined with unrelated CB were applied. And PTCY with or without a low dose of ATG rather than a regular dose of ATG in vivo T cell depletion in haplo-HSCT in our study (Li et al, 2019;Xiao et al, 2021). Consistently, a series of studies support CMV infection occurred more frequently in haplo-HSCT due to delayed T-cell reconstitution (Dziedzic et al, 2017;Lin et al, 2019;Yokoyama et al, 2019;Solano et al, 2021;Cho et al, 2021).…”
Section: Discussionsupporting
confidence: 82%
“…Notably, we reported that a higher incidence of CMV infection was found in ALL and AML compared to TM patients. The potential reasons included that more haplo-HSCTs were performed and more CB engraftments were found in leukemia patients compared to TM patients based on our transplant regimen ( Xiao et al., 2021 ). Our result was quite similar to a current study in which the cumulative incidences of CMV DNAemia in the MSD, MUD and haploidentical groups were 39.0, 55.6, and 85.7%, respectively ( Lin et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation